Propuesta de un manual de funciones, valuación de puestos por puntos y un reglamento de admisión y empleo basado en el modelo de competencias para el talento humano de la empresa Leadcom del Ecuador S.A. región 1, de la ciudad de Quito - Saritama Rodríguez, Juan Manuel (2015)
Human Resource area became the foundation of every business, you need a strong foundation to grow and adapt to great competition that national and international markets demand. Staff must be able to respond to any capacity since he has been charged, it is for this reason that the support of the company Leadcom of Ecuador SA Region 1, located in the city of Quito being a global leader in the provision, management and implementation services and integrated telecommunications, which was established in the year 2003, in addition to 165 workers solutions, have developed this project Thesis entitled: "" PROPOSAL FOR A MANUAL FF FUNCTIONS, VALUATION OF POSITIONS FOR POINTS AND REGULATION FF ADMISSION AND EMPLOYMENT BASED ON THE MODEL OF COMPETENCE FOR HUMAN TALENT COMPANY OF ECUADOR SA LEADCOM, REGION 1, CITY OF QUITO. "Where the overall objective is to design a proposal for a manual of functions, job evaluation points and regulations for admission and employment, based on the competency model for human talent Leadcom Company of Ecuador SA Region 1, of the city of Quito. For the sole purpose of assisting the reconstruction of the area of Talent and the enterprise to obtain a personal quality and satisfied with the benefit that the company offers. To reach the objective methods and techniques were used, as they are; the descriptive method used for the explanation of the current situation of the company and to draw conclusions and proposals, the inductive method - Deductive was used in the diagnosis of the problems of each department of the company, in deriving conclusions and drafting of possible solutions to their problems, and the Historical method was used for the description and evolution of the company, in order to obtain information; between the techniques used are; Surveys of department heads to enrich the diagnosis, targeting 165 employees surveys to determine the duties of their respective positions, an interview with the head of human talent to determine the status of the company and registration is studied on data functions jobs. For analysis of the results tabulation of the data obtained by interviewing techniques and surveys, which served to make the proposal manual functions are used; This manual helped in the valuation of positions which together with the equation of the straight line the new salaries were determined; For the rules of admission and employment through an investigation of the rules and regulations that are needed for the company as proposed; Besides the historical background to obtain data that were used for the structural and functional organization addressed. In the distribution of literals in the thesis itwas determineda) TITLEreferring to the question asked, b) ABSTRACT where one presented in an abbreviated form and precise content of the thesis, c) INTRODUCTION presented, described and analyzed conditions that led to the development of the thesis d) REVIEW OF LITERATURE different literature sources were reviewed to collect information necessary and relevant, e) MATERIALS AND METHODS essential for data collection and analysis of research instruments, f) is described RESULTS presented the results of the analysis performed by previous research., g) DISCUSSION fundamental point where proposals according to research obtained, h) CONCLUSIONS performed the research results so that you can appreciate the results are synthesized, i) Recommendations made to work with new complementary ideas to the original investigation and a future, j) REFERENCES books, manuscripts, websites, among others, that allowed the development of this research described k) where ANNEXES includes additional information such as the approved project plan, the format of the survey and interview, and pictures about the company study